KINERJA PENGHULU DALAM PELAYANAN SURAT KETERANGAN PINDAH BERDOMINISILI DI KEPENGHULUAN BANTAIAN KECAMATAN BATU HAMPAR KABUPATEN ROKAN HILIR - ", Alamsyah; ", Sujianto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Village massacre has implemented a variety of activities related to the public service and the service time. Furthermore, the duty of government officials to carry out public service penghoeloe optimal for each type of service. In many increased population growth in the District flagstones Kepenghuluan Bantayan In particular, they must take care of the transfer letter or care of moving domicile certificate in order for immigrants had no difficulty in dealing with issues relating to population and also for their interest sindiri. As an immigrant must be for them to take care of moving letter live so they can be known by the locals as well as residents of the They can be recognized by the local government.The concept of the theory is that researchers use performance theory, leadership and ministry. This study used qualitative research methods to study descriptive data in the data collection, the researcher used interview, observation and documentation. By using key informants as sources of information.The results showed that about prince Performance in Service Moving Letters explanation Domiciled In village slaughtered. The lack owned financial aid village exacerbated by the slowness of the government in providing funds, this delay makes the process of planned development is not in accordance with the original plan, the lack of community participation village to development that is part of a course of performance of the prince makes it increasingly difficult the success of the performance of the prince . Keywords: Performance, Services, and Moving Letters Ketereangan Domicile